2019
DOI: 10.3390/app9245493
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ground Reaction Forces, Joint Mechanics, and Stiffness during Treadmill Running to Fatigue

Abstract: Purpose: This study aimed to determine the changes in lower extremity biomechanics during running-induced fatigue intervention. Methods: Fourteen male recreational runners were required to run at 3.33 m/s until they could no longer continue running. Ground reaction forces (GRFs) and marker trajectories were recorded intermittently every 2 min to quantify the impact forces and the lower extremity kinematics and kinetics during the fatiguing run. Blood lactate concentration (BLa) was also collected before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…After 5 km treadmill running, the ROM of the knee sagittal plane showed a decreasing trend, as well as the sagittal plane of the hip joint during the stance phase of running. Previous studies [ 35 , 36 ] found that the joint ROM increased in a fatigued state, however, our statistical results are not consistent with this observation. This may be due to the large inter-individual variability in the kinematics of running.…”
Section: Discussioncontrasting
confidence: 99%
“…After 5 km treadmill running, the ROM of the knee sagittal plane showed a decreasing trend, as well as the sagittal plane of the hip joint during the stance phase of running. Previous studies [ 35 , 36 ] found that the joint ROM increased in a fatigued state, however, our statistical results are not consistent with this observation. This may be due to the large inter-individual variability in the kinematics of running.…”
Section: Discussioncontrasting
confidence: 99%
“…Exhaustion during prolonged running inevitably causes neuromuscular fatigue, which further leads to lower limb biomechanical changes [18]. Studies of biomechanical variability in post-fatigued are usually applied to unilateral limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term and high-intensity running unavoidably induces neuromuscular fatigue, which in turn affects the musculoskeletal system of the lower extremities. Generally, the motion control of the lower extremities decreases after fatigue, which is a major factor for running-related injuries [ 42 , 43 ]. It was expected that fatigue would influence the GRFs by altering the running state of the runners during a prolonged running session.…”
Section: Discussionmentioning
confidence: 99%